2021
DOI: 10.1155/2021/9912325
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Regulates Endoplasmic Reticulum Stress and Ameliorates Neuronal Injury in Rats with Acute Ischemic Stroke

Abstract: Ischemic stroke is a common cause of morbidity, mortality, and disability worldwide. Electroacupuncture (EA) is an effective method for alleviating brain damage after ischemic stroke. However, the underlying mechanism has not been fully elucidated. This study aimed to determine whether endoplasmic reticulum stress (ERS) could contribute to the protective effects of EA in cerebral ischemia/reperfusion injury (CIRI) to provide a rationale for the widespread clinical use of EA. Rats were divided into the sham-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Because of the complexity of the disease, combinations of acupuncture points increased the efficacy of EA compared with single acupuncture points. As shown in our previous studies, EA at the combination of the “Baihui” (GV20) and “Zusanli” (ST36) acupoints exerts synergistic protective effects on attenuating neuronal injury by suppressing endoplasmic reticulum stress and ameliorating mitochondrial functional damage in MCAO rats [ 40 , 50 ]. We demonstrated that the combination of two acupoints provided a significant protection against cerebral ischemic injury within seven days [ 51 ], especially on day 3.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the complexity of the disease, combinations of acupuncture points increased the efficacy of EA compared with single acupuncture points. As shown in our previous studies, EA at the combination of the “Baihui” (GV20) and “Zusanli” (ST36) acupoints exerts synergistic protective effects on attenuating neuronal injury by suppressing endoplasmic reticulum stress and ameliorating mitochondrial functional damage in MCAO rats [ 40 , 50 ]. We demonstrated that the combination of two acupoints provided a significant protection against cerebral ischemic injury within seven days [ 51 ], especially on day 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the cerebral cortex is involved in the antihyperalgesic effects of EA remains unclear. By regulating ERS, EA can alleviate neuronal apoptosis caused by ischemic stroke or spinal cord injury and promote the recovery of nerve function [ 43 , 44 ], providing a theoretical possibility for EA to alleviate NP by suppressing ERS. In the present study, we performed EA treatment from days 0 to 6 for 30 min/day.…”
Section: Discussionmentioning
confidence: 99%
“…[56] Also, cerebral IR injury induces neuronal apoptosis in brain tissue. [57] Transient common carotid arteries occlusion increases Fluoro-Jade B + cells, a fluorescent marker of cellular degeneration or death, in the hippocampus. [55] In agreement with these findings, we found that IR for 8 min resulted in a decrease in the number of neurons in all hippocampal regions.…”
Section: Effect Of P Reptans Root Extract On Inhibitory Passive Avoid...mentioning
confidence: 99%